A comparison of the impact on neuronal transcriptome and cognition of rAAV5 transduction with three different doses in the mouse hippocampus - Liu, Yi-Si; Wang, Meng-Ling; Hu, Neng-Yuan; Li, Zi-Ming; Wu, Jia-Li; Li, Hao; Li, Jing-Ting; Li, Xiao-Wen; Yang, Jian-Ming; Gao, Tian-Ming; Chen, Yi-Hua (Frontiers in Molecular Neuroscience, 2023)
Introduction Recombinant adeno-associated viruses (rAAVs) are widely used in genetic therapeutics. AAV5 has shown superior transduction efficiency, targeting neurons and glial cells in primate brains. Nonetheless, the comprehensive impact of AAV5 transduction on molecular and behavioral alterations remains unexplored. This study focuses on evaluating the effects of AAV5 transduction in the hippocampus, a critical region for memory formation and emotional processes. Methods In this experiment, fluorescence-activated cell sorting (FACS) was utilized to isolate the mCherry-labeled pyramidal neurons in the hippocampus of CaMkIIα-cre mice following three different doses rAAV5-mCherry infusion after 3 weeks, which were then subjected to RNA sequencing (RNA-seq) to assess gene expression profiles. The cytokines concentration, mRNA expression, and glial response in hippocampi were confirmed by ELASA, digital droplet PCR and immunohistochemistry respectively. Locomotion and anxiety-like behaviors were elevated by Open Field Test and Elevated Plus Maze Test, while the Y-Maze were used to assessed spatial working memory. Recognition memory and fear responses were examined by the Novel Object Recognition Test and Fear Conditioning Test, respectively. Results We found that 2.88 × 1010 v.g rAAV5 transduction significantly upregulated genes related to the immune response and apoptosis, and downregulated genes associated with mitochondrial function and synaptic plasticity in hippocampal pyramidal neurons, while did not induce neuronal loss and gliosis compared with 2.88 × 109 v.g and 2.88 × 108 v.g. Furthermore, the same doses impaired working memory and contextual fear memory, without effects on locomotion and anxiety-related behaviors. Discussion Our findings highlight the detrimental impact of high-dose administration compared to median-dose or low-dose, resulting in increased neural vulnerability and impaired memory. Therefore, when considering the expression effectiveness of exogenous genes, it is crucial to also take potential side effects into account in clinical settings. However, the precise molecular mechanisms underlying these drawbacks of high-dose rAAV5-mCherry still require further investigation in future studies.